2016
DOI: 10.3928/01477447-20160421-06
|View full text |Cite
|
Sign up to set email alerts
|

History of Nocturia May Guide Urinary Catheterization for Total Joint Arthroplasty

Abstract: Urinary tract infection is a common complication after total knee arthroplasty (TKA) and can be related to urethral catheterization. This study attempted to determine whether nocturia could be used as an indicator of risk for postoperative urinary retention to limit the need for prophylactic catheterization in men undergoing TKA. A retrospective study was performed in a consecutive series of men undergoing TKA at a single Veterans Affairs medical center. Patients reporting 0 episodes or 1 episode of nocturia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A retrospective study [34] which included 100 male patients who underwent primary TKA with indwelling urinary catheters concluded that the history of nocturia could be an effective screening tool for the safe elimination of indwelling catheterisation prior surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study [34] which included 100 male patients who underwent primary TKA with indwelling urinary catheters concluded that the history of nocturia could be an effective screening tool for the safe elimination of indwelling catheterisation prior surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Several risk factors have been defined for this complication, such as patient age, male gender and history of urologic obstructive disease. Moreover, the usage of a urinary catheter is linked to an increased risk of UTIs and prosthetic joint infections [5,6,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified increasing patient age as a significant risk factor for the onset of POUR [ 12 , 14 , 15 , [22] , [23] , [24] ], and male sex is equally well-described as a predisposing factor [ 12 , 14 , 15 , 25 ]. Other commonly identified risk factors include administration of high volumes of fluid intraoperatively and postoperatively [ [12] , [13] , [14] , 23 , 26 ], previous history of urologic disease such as benign prostatic hyperplasia or weak urinary stream [ [13] , [14] , [15] , [24] , [25] , [26] , [27] , [28] , [29] ], intraoperative catheter placement [ 23 ], the use of opioid analgesics during or after surgery (especially patient-controlled analgesia) [ 12 , 14 , 25 , 30 , 31 ], spinal or epidural anesthesia [ [11] , [12] , [13] , [14] ], poor ASA grade [ 14 ], and other medical comorbidities such as diabetes, renal disease, or even psychiatric disease [ 14 , 15 ]. Most of these factors are consistent with what is expected physiologically.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of urinary tract infection following bladder catheterization post-arthroplasty is a significant concern, given its status as a well-recognized post-operative complication [ 29 , 30 ]. Hematogenous spread from the urinary tract poses the potential threat of infecting the prosthetic joint or causing systemic dissemination, leading to severe complications, like sepsis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%